Politizar la traducción clásica chilena: ‘La Salvación de las Repúblicas de América’ en la esfera hispanohablante (1887-1939) - Sofía González Arancibia (Nuevo mundo - Mundos Nuevos, 2025)
What was discussed in political terms when the first translations from ancient Greek and Latin appeared in Chile at the early 20th century? This article presents the public and private readings of these translations by literary critics. This focus on audience interpretation led to the application of conceptual history of politics to the analysis of famous examples from the textual corpus. The research proposes that the audience was interested in two areas of the texts, which were the translational value of a work of art translated with fidelity to the original author, and the cultural role in an environment of decadence of the Latin language. The study concludes that the critics publicized the political prestige that translating the Greek and Latin classics into Spanish meant during a war context.